2021
DOI: 10.1007/s00330-021-07698-z
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast-enhanced MRI of synovitis in knee osteoarthritis: repeatability, discrimination and sensitivity to change in a prospective experimental study

Abstract: Objectives Evaluate test-retest repeatability, ability to discriminate between osteoarthritic and healthy participants, and sensitivity to change over 6 months, of dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) biomarkers in knee OA. Methods Fourteen individuals aged 40–60 with mild-moderate knee OA and 6 age-matched healthy volunteers (HV) underwent DCE-MRI at 3 T at baseline, 1 month and 6 months. Voxelwise pharmacokinetic modelling of dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…For example, some scholars have explored the diagnostic value of the total knee MRI scores for knee OA and found that the whole-organ MRI score (WORMS) was positively correlated with Western Ontario and Mc Master University Osteoarthritis Index (WOMAC) score, indicating that the pain, stiffness, and function of patients with the knee OA can be explained by imaging, and multiple linear regression analysis has been confirmed [18,19]. However, some scholars have accurately measured the T2 of cartilage in each area of the knee joint using T2 maps generated by MR sagittal T2 mapping imaging sequences and found that cartilage T2 values were increased and weight-bearing areas were significant in patients with OA, but there was no significant correlation between clinical scores and cartilage T2 changes in all subjects [20]. In summary, further studies and confirmation are needed regarding the correlation between MRI findings and clinical symptoms.…”
Section: Introductionmentioning
confidence: 93%
“…For example, some scholars have explored the diagnostic value of the total knee MRI scores for knee OA and found that the whole-organ MRI score (WORMS) was positively correlated with Western Ontario and Mc Master University Osteoarthritis Index (WOMAC) score, indicating that the pain, stiffness, and function of patients with the knee OA can be explained by imaging, and multiple linear regression analysis has been confirmed [18,19]. However, some scholars have accurately measured the T2 of cartilage in each area of the knee joint using T2 maps generated by MR sagittal T2 mapping imaging sequences and found that cartilage T2 values were increased and weight-bearing areas were significant in patients with OA, but there was no significant correlation between clinical scores and cartilage T2 changes in all subjects [20]. In summary, further studies and confirmation are needed regarding the correlation between MRI findings and clinical symptoms.…”
Section: Introductionmentioning
confidence: 93%
“…Using a longitudinal study with up to 6 months of follow-up, MacKay et al determined the repeatability, discriminatory power, and sensitivity to change DCE for imaging synovitis in the knee. 51 They found that for all outcomes, K trans performed the best of all DCE-MRI derived imaging. In the 6month period, 5 of 12 OA patients showed a change in K trans above the smallest detectable difference.…”
Section: Dynamic Contrast-enhanced Mrimentioning
confidence: 99%
“…K trans has demonstrated greater test-retest repeatability and ability to detect changes in the inflamed synovium of knees with OA compared with IAUC 60 and STV. 10 Since K trans is a composite measure of blood flow and capillary permeability, 11 which both positively correlate with inflammatory activity, K trans can be used to quantify the intensity of synovitis. However, while DCE-MRI is effective at evaluating synovitis, it requires longer scan times along with increased costs due to the use of contrast agent.…”
Section: Introductionmentioning
confidence: 99%
“…However, these approaches do not provide any insight into the intensity of synovitis, which may be a more responsive measure and correlate more strongly with symptoms than the extent of synovitis 9 . Dynamic contrast‐enhanced (DCE)‐MRI with administration of GBCA has previously been used to evaluate synovitis in subjects with knee OA 10 using several biomarkers, including the initial area under the time‐concentration curve at 60 s (IAUC 60 ), the synovial tissue volume (STV), and the pharmacokinetic parameter K trans , which is the volume transfer coefficient between blood plasma and the extracellular extravascular space. K trans has demonstrated greater test‐retest repeatability and ability to detect changes in the inflamed synovium of knees with OA compared with IAUC 60 and STV 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation